A novel assessment, diagnostic and treatment system for diabetic foot - Jordi Viadé; Maria Nicolás; Magdalena Bundó; Marc Sirvent; Clàudia Riera; Miquel Sabriá (Journal of Foot and Ankle Research, 2023)
Abstract Background This report aims to present a novel system for the management of foot lesions in patients with diabetes. It was developed in the diabetic foot unit (DFU) of the Mutua de Terrassa University Hospital (HUMT) by primary care professionals, the Diabetic Foot Clinic (DFC), and during emergency cases treated by our group based on daily activities in patients with neuropathy or neuroischemia. Body This system considers five degrees of action based on two fixed variables: presence of infection and lesion depth. These two variables allowed the user to investigate aspects of the system until the overall action required by the pathology is made clear. These variables establish pathology stages of various severities that require different actions in aspects of care, management and treatment. Conclusion This tool facilitates diagnosis, treatment, and coordination among different members of a multidisciplinary team working in specialized hospital units, primary care centers, and emergency settings.